(untitled) - Newman, Michael C. (Boca Raton, FL, 2002)
Completely revised and updated, Fundamentals of Ecotoxicology, Second Edition presents a treatment of ecotoxicology ranging from molecular to global perspectives. The authors focus first on lower levels of organization and then extend their discussion to include landscape, regional, and biospheric topics, imparting a perspective as broad as the the problems facing practicing professionals. See what's new in this edition:·A comprehensive chapter on the nature, transport, and fate of major classes of contaminants in terrestrial, freshwater, and marine systems ·Side bars containing vignettes by leaders in the field let you benefit from the experience of diverse practitioners in the field·An appendix covering European environmental regulationsThe authors detail key contaminants of concern, explore their fate and cycling in the biosphere, and discuss bioaccumulation and the effects of contaminants at increasing levels of ecological organization. They cover regulatory aspects of the field in separate chapters that address the technical issues of risk assessment and discuss key U.S. and European legislation in the appendices. Complete with study questions, a detailed glossary, and vignettes by various experts exploring special topics in ecotoxicology, Fundamentals of Ecotoxicology, Second Edition is an ideal introductory textbook for both undergraduate- and graduate-level courses, as well as a valuable reference for professionals.
Chu chuyển và tồn lưu độc chất trong hệ sinh thái,Ðộc chất học môi trường
Keywords: Pollution,Pollution; Environmental aspects,Health aspects